Alfabetização Científica com Modelagem Matemática nos anos iniciais do Ensino Fundamental - Silva, Simone Ribeiro da (2023)
Mathematical Modeling and Scientific Literacy are expressions that come from different areas: the first is widely discussed in Mathematics Education, while the second in Science Education. However, the possibility of articulating them has been the focus, albeit subtle, of research in both areas. Thus, this research work focuses on Scientific Literacy and Mathematical Modeling, investigated from the realization of Modeling activities with students. The general objective of the research is to investigate which aspects of Scientific Literacy emerge from the activities of students when they perform activities of Mathematical Modeling. In this sense, we seek to answer the following research question: What characteristics of Scientific Literacy are shown in the productions of students in the early years of Elementary School when experiencing Mathematical Modeling activities? To this end, the methodological course was structured by the development of a Scientific Initiation project, as a methodological strategy, with students from a fifth year of the initial years of Elementary School, by the elaboration of problematic situations to develop Mathematical Modeling practices and by the production, collection and data analysis, which are made up of the students' written productions and oral manifestations, while developing Modeling activities. Data analysis is carried out considering a framework of eight signaling aspects of the process of Scientific Literacy in Mathematical Modeling, constructed through a literature review and theoretical articulations on Scientific Literacy and Mathematical Modeling. With the completion of the analysis stage, which we organize and describe in terms of local analysis and global analysis, we evidenced three aspects of Scientific Literacy made possible with the development of the analyzed Modeling activities, which are: knowledge aspect, strategies aspect and sensibilitie aspect for the investigation. Given this analysis process, we point out six characteristics of Scientific Literacy that emerged in the students' productions when developing Mathematical Modeling activities during the project